Trastuzumab emtansine (T-DM1)-associated cardiotoxicity: Pooled analysis in advanced HER2-positive breast cancer. (February 2020) - Pondé, Noam; Ameye, Lieveke; Lambertini, Matteo; Paesmans, Marianne; Piccart, Martine; de Azambuja, Evandro
Abstract: Introduction: T-DM1 has been approved for the treatment of HER2+ breast cancer. Cardiac dysfunction is a side effect of trastuzumab, a component of T-DM1. However, little is known about T-DM1-associated cardiotoxicity. Methods: We have conducted a pooled analysis of T-DM1 trials in advanced HER2+ breast cancer cases to understand the incidence, clinical presentation as well as to establish possible risk factors for T-DM1-associated cardiotoxicity. The primary endpoint was the incidence of cardiac events (CEs). CEs were categorized as follows: (1) congestive heart failure (CHF) or grade 3/4 LVEF drop; (2) cardiac ischemia, (3) cardiac arrhythmia, (4) grade 1/2 LVEF drop. Secondary endpoints included CE recovery rate and impact of CEs on treatment discontinuation. Logistic regression was used to assess possible risk factors for CEs. Results: Individual patient-level data from 1961 patients exposed to T-DM1 in seven trials were pooled. Of these, 1544 received T-DM1 and 417 T-DM1 + pertuzumab. CHF/LVEF drop grade 3/4 was reported in 0.71%, cardiac ischemia in 0.1%, cardiac arrhythmia in 0.71% and grade 1/2 LVEF drop in 2.04%. The total CE rate was 3.37% (95% confidence interval (CI), 2.6%–4.3%). Multivariate analysis showed patient's age ≥65 (OR 3.0; 95% CI, 1.77–5.14; P -value <0.001) and baseline LVEF<55% (OR 2.62; 95% CI, 1.29–5.32; P -value 0.008) as risk factors. CEs resolved in most (79%) patients after treatment discontinuation. Conclusion: The incidence of CEs in patients receiving T-DM1 was low. Older patients receiving T-DM1 should be carefully followed for cardiac safety during treatment. Highlights: Little is known about cardiac toxicity during T-DM1 treatment. This is a pooled analysis comprising 1961 patients exposed to T-DM, 1 investigating cardiac events. The total cardiac event rate was 3.37%, mostly asymptomatic LVEF drops. Cardiac events can occur during T-DM1 treatment but are rare.